Plasma fibrinogen: An independent predictor of pediatric appendicitis - M S Vinod Kumar; Mannu Kumar Tiwari; Jasdeep Singh; Anil Malik (Wolters Kluwer Medknow Publications, 2021)
Aims: Appendicitis, in spite of all the diagnostic advances, achieving an accurate and timely diagnosis of this common condition in children remains a challenge. Plasma fibrinogen (FB) is an acute inflammatory mediator and has been proposed and evaluated as an adjunct laboratory marker for improving diagnostic accuracy. The study evaluates the plasma values of Se FB along with other serum markers in pediatric appendicitis patients, to determine their diagnostic accuracy. Methods: Prospective observational study on 120 patients between the age group of 5 and 12 years. All eligible enrolled cases underwent total leukocyte count (TLC), plasma FB, C reactive protein (CRP), neutrophil-lymphocyte ratio (NLR), absolute neutrophil count (ANC), and erythrocyte sedimentation rate on admission along with pediatric appendicitis score. Final confirmation of diagnosis and allotment of cohort was made by intra operative findings and histopathological confirmation. Two groups were defined: (1) Histopathologically confirmed acute appendicitis-Cases (2) Nonspecific abdominal pain-Controls. Laboratory results were statistically analyzed between the case and the control groups for diagnostic accuracy. Results: Study reflected strong statistical significance in terms of leukocyte count, ANC, NLR, CRP, and FB levels. However, plasma FB (value above 4.02 g/L) had the highest diagnostic accuracy rate of 82.50% compared to other laboratory values (TLC-70.83%, CRP-70.00%). Conclusion: Plasma FB has emerged as an accurate diagnostic tool and its diagnostic accuracy is superior to all other laboratory parameter studied (TLC, CRP, NLR, and ANC). Plasma FB values above 4.02 g/L is an independent predictor of appendicitis and can help in reducing negative laparotomy in pediatric age group.